Indium concentration in serum is an excellent predictor for assessing accumulated indium concentration in the lungs - Hirata, Miyuki (J Occup Health, 2021)
OBJECTIVE: To clarify whether indium in serum (In‐S) is an appropriate parameter for assessing accumulated indium concentration in the lungs (In‐L). METHODS: During our approximately 15‐year Japanese cohort follow‐up, five male indium‐tin oxide (ITO) or/and indium trioxide‐exposed workers underwent lung surgical procedures to treat lung diseases or to confirm a diagnosis of lung impairments. We measured In‐L of these Cases 1‐5 and were able to assess the relationship between In‐L and the most recent In‐S. Another 1 Japanese case (Case 6) exposed to indium trioxide and indium hydroxide was referred from an article. RESULTS: Cases 1 and 3 had lung cancer, Case 2 suffered from recurrent pneumothorax, and Case 4 had interstitial pneumonia with mild emphysema. Case 5 had severe emphysema with pulmonary hypertension and underwent bilateral lung transplantation. In Cases 1‐5, In‐L and In‐S ranged from 3.4 to 161.2 µg/g wet weight and 0.7 to 60.4 ng/mL, respectively, and In‐L/In‐S ratios ranged from 2484 to 4857. The slope of the single regression equation with zero intercept was 2767 and the correlation coefficient was 0.995. In contrast, Case 6 was extraordinarily outlying, but the reason is unclear. CONCLUSIONS: In‐S is an excellent predictor for assessing indium load in the lungs in ITO or/and indium trioxide‐exposed workers. However, number of cases was only five and not enough to authorize definite conclusion. It is desirable to add more cases to confirm our conclusion.